Discursos de gênero e liderança na reportagem da revista Exame sobre cotas para executivas na cúpula das empresas - Dias, Adriana Faria de Alcântara (2016)
With the new labor demands, new careers are emerging. In this context, a growing number of women are actively participating in the labor market, who are also achieving, even in small numbers, some positions at the top of companies. The everyday life is not easy for women who face lots of prejudice and discrimination in the workplace. This study brings women to the center, especially those who occupy positions of power in society, i.e. executive women. Thus, this research aims to analyze the discourses of gender and leadership in a report published in Exame magazine dated June 10th, 2015, the data generation instrument in this study. The investigation was based in the concept of language as performative speech acts (AUSTIN, 1962; DERRIDA, 1972), the perspective of gender as a social, historical and performative construction (BUTLER, 2003; LOURO, 2003), and the concept of leadership according to Vergana (2007), Mitchell (2008) and Costa Reis et al. (2013). For the analysis of gender and leadership speeches, we utilized linguistic indexes proposed by Silverstein (2003). The analyzes of the report show discourses of gender and leadership. Based on the gender discourse analyzed in the survey, the report "Quota for women?" points to speeches about prejudice and female feelings of inferiority in relation to men. Women are still constructed by means of performative speech acts as less capable than men to occupy leadership positions, or that women should serve men. Another emerging discourse concerns to the quota system, understood as necessary by the speeches of the women cited by the report, but as inefficient by the magazine that, in order to prove it, resorts to performative speech acts by specialists. Another gender discourse is related to motherhood. According to the report, women lose the opportunity to occupy certain positions in companies because they often opt to devote themselves to their children. This discourse also suggests that women are to blame for their professional failure, and that motherhood is an obstacle to success. In leadership discourses we observe women who reached the top of companies and are a reference in the business market, as well as foreign women who are considered as examples of professional growth.